A note on implementing the Durbin and Koopman simulation smoother - Marek Jarociński (European Central Bank (ECB), 2015)
The correct implementation of the Durbin and Koopman simulation smoother is explained. A possible misunderstanding is pointed out and clarified for both the basic state space model with a non-zero mean of the initial state and with time-varying intercepts (mean adjustments).
Keywords: C3; C15; 330; simulation smoother; state space model; trend output